Vitamin A - Queiroz Zepka, Leila; Vera de Rosso, Veridiana; Jacob-Lopes, Eduardo (Biochemistry, 2019)
This book is the most up-to-date research on vitamin A. It is designed for scientists and researchers to deepen their knowledge in this critical knowledge field, and it is a solid resource that brings together multidisciplinary research, development and innovation for a varied analysis of vitamin A.